Machine learning enabled multivariate analysis of neuroimages - Chen, Dawen (2016)
This project attempted to investigate various methods of multi-variant analysis in order to understand network effects of human brains. A literature review on forefront of research in the field of brain network was conducted, especially about functional connectivity analysis. The review was from classical statistical analysis to more advanced correlation-based analysis. It also covered the most recent breakthrough, brain fingerprinting which is to identify people by their neural activation profile.